Quadruple hydrogen bonds and thermo-triggered hydrophobic interactions generate dynamic hydrogels to modulate transplanted cell retention. (13th March 2019) - Liu, Sa; Qi, Dawei; Chen, Yunhua; Teng, Lijing; Jia, Yongguang; Ren, Li
Abstract : Supramolecular dynamic hydrogels with quadruple hydrogen bonds and thermo-triggered hydrophobic interactions demonstrate a promising capability of modulating transplanted cell retention. Abstract : A supramolecular hybrid hydrogel displaying a wide array of dynamic physical properties along with enhanced in vivo stem cell retention has been developed. The key strategy is facilely polymerizing bioactive gelatin methacrylate (GelMA) with 2-(2-methoxyethoxy)ethyl methacrylate (MEO2 MA) and 2-(3-(6-methyl-4-oxo-1, 4-dihydropyrimidin-2-yl)ureido)ethyl methacrylate (UPyMA) to generate one hybrid branched copolymer. Rapid gelation occurs upon increasing the temperature above the lower critical solution temperature (LCST) of this supramolecular copolymer, where PMEO2 MA segments dehydrate and assemble into clusters, providing a hydrophobic microenvironment facilitating UPy dimerization to connect polymer chains, thus forming quadruple hydrogen bond reinforced crosslinking networks. The biodegradable, self-healing, thermo-reversible and injectable properties of the supramolecular hydrogel are finely tunable by changing the hydrogel formulation. Mesenchymal stem cells encapsulated in the hydrogel show high viability and proliferation. The subcutaneous study shows that the stem cells delivered within the in situ formed hydrogel are well protected from mechanical damage and have significantly enhanced in vivo cell retention for three weeks. These results suggest that the dynamic supramolecular hydrogel can be utilized to regulate stem cells for tissue regeneration applications.